The role of visual language in China’s new era: beyond cultural communication - Xiaoren Chen (Trans/Form/Ação)
In the past few decades, interdisciplinary research has become a trend. Visual language and cultural thinking are two different concepts, each with its own unique research methods and theoretical frameworks. However, researchers are increasingly realizing that combining visual language and cultural thinking can provide a more comprehensive and in-depth understanding and analysis. The significance of this research is to broaden people's understanding of visual language and cultural thinking. Through interdisciplinary exploration, the cultural connotations and meanings behind images can be deeply explored to reveal the differences and commonalities among different cultures, which helps deepen people's awareness of cultural diversity and promote exchanges and understanding among different cultures. It can be used as a resource for social development and it can have a significant impact on economic development, resulting in a new cultural thinking. At the same time, it is also a core factor of technological power. As an element and symbol of soft culture, language can play a role in public diplomacy and participate in cultural thinking and competition. As human society enters the era of Internet media, people’s language equipment and language life have made significant progress.